2015
DOI: 10.1371/journal.pone.0117806
|View full text |Cite
|
Sign up to set email alerts
|

Akacid Medical Formulation Induces Apoptosis in Myeloid and Lymphatic Leukemic Cell Lines In Vitro and In Vivo

Abstract: Akacid medical formulation (AMF) is an oligoguanidine that exerts biocidal activity against airborne and surface microorganisms including bacteria, viruses, fungi, and molds, while showing relatively low toxicity to humans. We have previously shown that AMF exerts antiproliferative effects on a variety of solid tumor cell lines. In this study we raised the question whether AMF could also substantially inhibit cell growth or induce apoptosis in cell lines derived from hematologic malignancies such as leukemia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…38 In another study, they also reported that AMF has antiproliferative effects on cell lines derived from human leukemia and lymphoma and demonstrated that AMF induced caspase 8, −9 and −3/−7 and caused apoptosis both intrinsically and extrinsically. 39 These findings were found to be compatible with the results we obtained in this study. Mafra et al evaluated the cytotoxic effects of CHG and PHMB; although both solutions were found to have toxic effects on HUVEC and HCEC, similar to our results, the cytotoxic effects of PHMB occur through apoptosis, while CHG increases necrosis.…”
Section: Discussionsupporting
confidence: 92%
“…38 In another study, they also reported that AMF has antiproliferative effects on cell lines derived from human leukemia and lymphoma and demonstrated that AMF induced caspase 8, −9 and −3/−7 and caused apoptosis both intrinsically and extrinsically. 39 These findings were found to be compatible with the results we obtained in this study. Mafra et al evaluated the cytotoxic effects of CHG and PHMB; although both solutions were found to have toxic effects on HUVEC and HCEC, similar to our results, the cytotoxic effects of PHMB occur through apoptosis, while CHG increases necrosis.…”
Section: Discussionsupporting
confidence: 92%
“…This was compared to the counts of the total population, including G1‐/S‐/G2‐phase cells. For assessment of annexin V and PI, we used the Annexin V‐FITC Apoptosis Detection Kit (Enzo Lifescience Inc., Lausen, Austria) according to the manufacturer´s protocol as previously described .…”
Section: Methodsmentioning
confidence: 99%